Risk of disability in elderly diabetic patients - Marengo, Claudio; Comoglio, Marco (SEEd Srl, 2011)
The book provides an overview of the most common diabetes-related complications, supporting the clinician in the management of type 2 diabetes in the elderly: from the diagnosis of each complication, to the role of the pharmacological and non-pharmacological interventions.